Steroids for otitis media with effusion: a systematic review. - Butler, C; van Der Voort, J (2001)
BACKGROUND: Otitis media with effusion (OME) is common and may cause hearing loss with associated delayed language development in children. Treatment remains controversial. OBJECTIVE: To examine evidence for or against treating OME with systemic or topical nasal steroids. DATA SOURCES: We searched the Cochrane Controlled Trials Register using the terms otitis media; otitis media with effusion; glue ear; or OME and steroids; glucocorticoids; glucocorticoids, synthetic; glucocorticoids, topical; or anti-inflammatory agents, steroidal; or various combinations of these terms. EMBASE and MEDLINE were also searched. STUDY SELECTION: Randomized controlled trials of oral and topical nasal steroids, either alone or in combination with another agent such as an antibiotic, were included. Ten studies met the inclusion criteria. DATA EXTRACTION: Data extraction and methodological quality assessment were performed by the 2 of us (C.C.B. and J.H.v.d.V.) independently, using standardized methods described in the Cochrane Collaboration Handbook. DATA SYNTHESIS: The odds ratio for OME persisting after short-term follow-up in children treated with oral steroids compared with a control was 0.22 (95% confidence interval, 0.08 = 0.63), and was 0.32 (95% confidence interval, 0.20 = 0.52) for children treated with oral steroids plus an antibiotic compared with a control plus an antibiotic. Trends favored steroids for most other comparisons, but confidence intervals included unity. Trends favored steroids for most other comparisons, but confidence intervals included unity. CONCLUSIONS: Steroids alone or combined with an antibiotic lead to a quicker resolution of OME in the short-term. However, there is no evidence for a long-term benefit from treating hearing loss associated with OME with either oral or topical nasal steroids. These treatments are, therefore, not recommended.